Recombinant CV-A6 strains related to hand-foot-mouth disease and herpangina at primary care centers (Barcelona, Spain). (29th April 2019) - Andrés, Cristina; Guasch, Eulàlia; Piñana, Maria; Fernandes, Paula; Gimferrer, Laura; Esso, Diego Van; Codina, Maria Gema; Esperalba, Juliana; Vila, Jorgina; Rodrigo, Carlos; Martín, Maria Carmen; Fuentes, Francisco; et al.
Aim: To describe the genetic diversity of enteroviruses (EV) causing hand, foot and mouth disease (HFMD) and herpangina, especially of coxsackievirus (CV)-A6, from patients attended at pediatric primary care centers during the 2017–2018 season.Methods: Phylogenetic analysis of partial VP1 region was performed for genetic characterization. The complete VP1 and 3Dpol proteins were sequenced for lineage determination and detection of recombination events.Results: An 80% of samples were EV laboratory-confirmed. CV-A6 was the most detected (70%) and associated with atypical HFMD (78%). The comparison of VP1 and 3Dpol phylogenies showed evidence of recombination in three strains, in which two shifted to CV-A16 3Dpol.Conclusion: The study provides recent information regarding the nonrecombinant and recombinant EVs related to HFMD at primary care centers.